Analysis of the Balanced Scorecard Method as an Alternative Measuring Performance at Madiun City Land Office - Adhisya Maretha Ratnasti; Zaim Arif Eko Saputra (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2024)
This study aims to analyze and evaluate the results of using the Balanced Scorecard method as an alternative approach for measuring performance at the Madiun City Land Office. The research employed a mixed-methods approach, combining both quantitative and qualitative methods. The mixed-methods approach was applied to analyze the data, instead of providing a comprehensive overview of organizational performance, assessed quantitatively and qualitatively, focusing on customer perspectives and internal business processes. After analyzing the data using the Balanced Scorecard method, the result shows several insights. From a financial perspective, the analysis shows an economic ratio indicating overall positive results. The effectiveness ratio was relatively strong in 2020, and continued to show good results from 2021 to 2023. Additionally, the efficiency calculations suggest that the office falls into the highly efficient category. In terms of the customer perspective, the data drawn from the Public Satisfaction Index reveal unfavorable results in 2021, followed by very good results in 2022 and 2023. The internal business process perspective, assessed through benchmarks for innovation and infrastructure, indicates that overall conditions are good. Finally, the learning and growth perspective, which measures the level of employee training, reveals that only one employee participated in training in 2023. The overall employee turnover rate appears positive, while employee productivity levels show some fluctuations.